PENGARUH LINGKUNGAN DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DI POLITEKNIK PARIWISATA MEDAN - Lince Marcellina Hutabarat; Marudut Sianturi; Nikous Soter Sihombing (JURNAL ILMIAH SOCIO SECRETUM, 2022)
Employee performance can be influenced by many factors, including motivation, talent, interests, satisfaction, and experience, as well as factors that come from outside the individual employess such as supervision, salary, work environment, employment opportunities, and promotions. But this study is limited only to work environment factors and job satisfaction. This type of research is quantitative descriptive and explanatory research. This research was conducted at the Medan Tourism Polytechnic, with a population of 101 employess, taking research samples using the sloving formula, so the sample in this study amounted to 81 people. Data collection techniques by conducting interviews and observation with questionnaire media. While the data analysis technique used is the classic assumption test, multiple linear regression, t test, F test and coefficient of determination. The results of this study are the influence of the Work Environment (X1) The Value of the t count of work environment is 2.486 and the value of t table is 1.664 the t count > t table (2.486>1.664) and the sig value<0.05 (0.015<0.05), so that the work environment partially has a positive and significant effect on the performance of the Tourism Polytechnic employees. There is the influence of job satisfaction (X2), the value of the titung variable job satisfaction is 4.135 and the t table value is 1.664, then the t count> t table (4.135>1.664) and the sig value <0.005 (0.000<0.005) so it can be concluded that work partially has a positive and significant effect on the performance of employees at the Medan Tourism Polytechnic. The results of the F test (Simultaneous Test) show that the value of F count is 35,025 with a significant level of 95% (=0.05) is 2.72 where (F count> F table) so that 35,025>2,72 and the sig value <0,05 (0,000< 0,05). This simultaneously there is a significant influence between work environment variables (X1) and the job satisfaction (X2) on the performance of Medan Tourism Polytechnic Employees.